Socially engaged public art in East Asia : space, place, and community in action - Wang, Meiqin, 1974- (Vernon series in art., 2022)
"This anthology elucidates the historical, global, and regional connections, as well as current manifestations, of socially engaged public art (SEPA) in East Asia. It covers case studies and theoretical inquiries on artistic practices from Hong Kong, Japan, mainland China, South Korea, and Taiwan with a focus on the period since the 2000s. It examines how public art has been employed by artists, curators, ordinary citizens, and grassroots organizations in the region to raise awareness of prevailing social problems, foster collaborations among people of varying backgrounds, establish alternative value systems and social relations, and stimulate action to advance changes in real life situations. It argues that through the endeavors of critically-minded art professionals, public art has become artivism as it ventures into an expanded field of transdisciplinary practices, a site of new possibilities where disparate domains such as aesthetics, sustainability, placemaking, social justice, and politics interact and where people work together to activate space, place, and community in a way that impacts the everyday lives of ordinary people"--